Taking Deliberation to the Streets: Reflections on Deliberative Walks - Raisio, Harri; Ehrström, Peter (Scandinavian Journal of Public Administration, 2017)
The focus of this article, a model that we call the Deliberative Walk, builds on the princi- ples of Citizens’ Juries and Development Walks. Two case studies are used to explore the potential of uniting the two different participatory models, one that is based on discussion and the other that is more observation oriented. Both case studies were implemented in Finland during autumn 2014. Reviewing these case studies is important, because the issue of ‘taking deliberation to the streets’ has rarely been addressed in the academic literature on CJs and other deliberative mini-publics. Based on the case studies, our suggestion is that in place-specific deliberations, a Deliberative Walk is a suitable method when the issue that is being tackled has highly intertwined social and physical dimensions, while in more situation-specific deliberations, a Deliberative Walk adds value when the issue is such that it needs a more complete and direct learning experience.